Necessity of Antibiotics following Simple Exodontia - Waqas Yousuf; Moiz Khan; Hasan Mehdi; Sana Mateen (Scientifica)
Introduction. The aim of our study is to assess the need for postoperative antibiotics following simple exodontia and determine its role in minimizing patient discomfort and postoperative complications. Material and Methods. All the patients undergoing simple extractions were grouped into two categories: Group 1, patients receiving antibiotics, and Group 2, patients receiving no antibiotics. Patients were recalled on the sixth day to assess postoperative complications. On recall, patients were evaluated for signs of persistent inflammation and signs of dry socket. Presence of persistent inflammation and/or suppuration on the 6th day was considered as wound infection. Results. A total of 146 patients were included in this study. Out of the total sample, 134 (91.8%) presented with no postoperative complications and 12 (8.2%) had postoperative complications, out of which 11 (7.5%) patients presented with dry socket (alveolar osteitis), 5 (3.4%) in the antibiotic group and 6 (4.1%) in the nonantibiotic group. Only 1 patient (0.7%) was reported with infection of the extraction socket in the nonantibiotic group, whereas no case of infection was found in the antibiotic group. Conclusion. Antibiotics are not required after simple extractions in patients who are not medically comprised nor do they have any role in preventing postoperative complications.